Situasi dan Kebutuhan Remaja Tentang Edukasi Kesehatan Reproduksi - Hannifah, Siti; Damayanti, Rita; Herawati, Titeu (Universitas Pahlawan Tuanku Tambusai, 2024)
Andir is one of district that has the highest HIV and AIDS cases in Bandung. According to Bandung AIDS Comission, it is confirmed that 224 PLWIH and estimated that 4,235 key populations, including sex workers, LGBTQ+, people who inject drugs live in the district. Young people in Andir has become on of the most risky population of HIV transmittion. The knowledge of sexual reproductive health, drug abuse and HIV prevention among these young population needs to be improved in order to decrease new HIV cases. The purpose of this rapid general assessment is to obtain a program design model that is right on target and according to the needs of youth.The method used in this assessment was to use a quantitative and qualitative approach involving 63 teenage respondents and 7 stakeholder informants. The results of the assessment revealed: 60% of adolescents understand reproductive health, 72% of respondents understand drugs, 60% of adolescents understand HIV and AIDS; the desired form is through social media; 89% of respondents had been involved in youth activities, 79% had been involved in planning an activity, and 62% of respondents had made decisions in activities; Facilities and infrastructure owned by the District and Kelurahan are Youth Space, Musrembang, community funds, Jurnal Ners Universitas Pahlawan ISSN 2580-2194 (Media Online)corporate concern funds; The facilities owned by the Puskesmas are funds sourced from the BLUD (Regional Public Service Agency), BOK (Health Operational Assistance), APBD (Regional Revenue and Expenditure Budget), and cooperation with other parties (sponsorship).The results of the assessment recommendations for youth and stakeholders include: regular information on reproductive health, drugs, HIV and AIDS through social media with youth involvement (meaningful youth involvement); Optimizing government facilities, community, CSR, BLUD (Regional Public Service Agency), BOK (Health Operational Assistance), APBD (Regional Revenue and Expenditure Budget), as well as the collaboration of academia, business, community, government and media (Pentahelix).Keywords: content, formatting, article